If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -17 = 4x + 4 Reorder the terms: -17 + x = 4x + 4 Reorder the terms: -17 + x = 4 + 4x Solving -17 + x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -17 + x + -4x = 4 + 4x + -4x Combine like terms: x + -4x = -3x -17 + -3x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -17 + -3x = 4 + 0 -17 + -3x = 4 Add '17' to each side of the equation. -17 + 17 + -3x = 4 + 17 Combine like terms: -17 + 17 = 0 0 + -3x = 4 + 17 -3x = 4 + 17 Combine like terms: 4 + 17 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 5x-2=6x+-8 | | 8x=8(x-1)+1 | | 4x^2+28x+50=0 | | 9d+35=4d | | x-3=5x+1 | | -1+4x-3x=7 | | (2k+1)=5(k-2) | | (2x-3y)(x-3y)= | | 250=14x+22x | | 4x-10+2x=62 | | 3(s+22)=4(s+2) | | 3(1-r)+5r=4(r+1)+5 | | 5+x+-3x=3x-2x-1 | | 3.4t+0.008=11 | | -x-30=3x+6 | | 45=3V | | -4r+5=2(2.5-2r) | | M^2+6m-16= | | 14-3(5t+-12)=1-(20t+1) | | 6z-4=9z+14 | | 8x+16=22+8x | | -33=r+(-26) | | (-5)+(9)= | | 14xy-7x^2+5x=0 | | x^2+10x+17=y | | (4x-2y)+70=180 | | 67=13+u | | 25c=675 | | (3m+6n)(7m+2n)= | | X+(x-10)=90 | | -8*+30=10 | | X^2+3x=13 |